Different Phenotypes of Mature Biofilm in Flavobacterium psychrophilum Share a Potential for Virulence That Differs from Planktonic State - Levipan, Héctor A.; Avendaño-Herrera, Ruben (Frontiers in Cellular and Infection Microbiology, 2017)
Flavobacterium psychrophilum is the etiological agent of bacterial coldwater disease and the rainbow trout fry syndrome in salmonid aquaculture worldwide. However, there have been few studies into the capacity of F. psychrophilum to form biofilms and how these cellular accretions differ from planktonic cells or how they affect potential virulence. We evaluated the biofilm formation by three Chilean isolates of F. psychrophilum (LM-02-Fp, LM-06-Fp and LM-13-Fp) and two non-Chilean strains (JIP02/86 and NCMB1947T), and compared biofilm and planktonic states to obtain insights into expression differences of virulence- and biofilm-related genes (VBRGs). Our findings are based on scanning confocal laser microscopy (SCLM) and LIVE/DEAD staining, enzymatic reactions, reverse transcription-quantitative PCR (RT-qPCR) of genes encoding putative virulence factors, and transcriptomes (RNA-Seq). The LM-02-Fp and NCMB1947T strains were the strongest and weakest biofilm producers, respectively. The strong-biofilm producer showed different physiological cell states distributed in different layers of mature biofilms, whereas the NCMB1947T biofilms consisted of cells arranged in a monolayer. WGA-binding exopolysaccharides would be the main components of their corresponding extracellular matrices. Transcriptomes of F. psychrophilum NCMB1947T and LM-02-Fp were clustered by state (biofilm versus planktonic) rather than by strain, indicating important state-dependent differences in gene expression. Analysis of differentially expressed genes between states identified putative VBRGs involved in polysaccharide biosynthesis, lateral gene transfer, membrane transport (e.g. for drugs and Fe3+), sensory mechanisms, and adhesion, and indicated that about 60 % to 100 % of VBRGs involved in these processes was significantly upregulated in the biofilm state. Conversely, upregulated motility-related genes in the biofilm state were not identified, whereas a lower fraction of proteolysis-related genes (33 %) was upregulated in biofilms. In summary, F. psychrophilum strains that produce different biofilm phenotypes show global transcriptional activity in the mature biofilm state that differs significantly from their planktonic counterparts. Also, different biofilm phenotypes share a genetic potential for virulence that is transcriptionally enhanced with respect to free-living cells. Our results suggest that the F. psychrophilum biofilm lifestyle acts as a reservoir for a given set of putative virulence factors, and recommend a deeper understanding of which could help prevent recurring infections in salmonid farms.